Path Planning Usage For Mobile Robots (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper deals with path planning programme for mobile robots. The aim of the paper is to develop a path planning programme for mobile robots that is based on simulation software development. The results of the careful analysis were considered for optimal path planning algorithms. The experimental evidence was proposed to demonstrate the effectiveness of the algorithm for steady covered space. The results described in this work can be extended in a number of directions, and applied to other algorithms.